Analisis Reaksi Pasar Modal Terhadap Perusahaan Perata Laba Dan Perusahaan Non Perata Laba Pada Perusahaan Sektor Pertanian Yang Go Publik Di Indonesia - Eksa Ridwansyah; Maryani Maryani (Politeknik Negeri Lampung, 2008)
This research is to analyze market response toward profit information issued by profit averaging or non profit-averaging company. The research was carried out through observation method. The data used were secondary data issued by Jakarta Stock Exchange (BEJ) and Indonesian Capital Market Directory. The variables were determined through unexpected earning and Cumulative Abnormal Return (CAR) methods. The model used in calculating expected profit was zero growth profit estimation and market expectation model. The result of the research showed that empirically all the hypotheses proposed were not proven or rejected. It can be concluded that the reaction of the stock exchange, as projected with abnormal return or stock trading volume between the company doing profit averaging and that of not doing, did not differ significantly. A similar result was also obtained when the profit averaging and non profit-averaging companies were classified based on positive and negative earning surprise. Keywords: unexpected earnings, Cumulative Abnormal Return (CAR), profit averaging.